Usher syndrome and psychiatric symptom : a challenge in psychiatric management - Rijavec, Nikolina (Array, 2009)
Usher syndrome, the most common case of deaf – blindness, may be associated with various psychiatric disorders. Inability of communication through spoken language in association with progressive visual impairment affects diagnostics and management in case of co-morbidity with mental disorder. A patient with Usher syndrome and psychiatric symptoms is described and the difficulties in psychiatric assessment in her case are discussed. A 28 years old woman with hearing impairment diagnosed at the age of 3 months and progressive pigmentary retinopathy diagnosed at the age of 19 years, has been treated for ADHD in childhood, eating disorder in adolescence and psychosis-like disorder in adult life